Problematics of Indonesian women migrant workes (towards a civilized country through the welfare state from a Pancasila perspective) - Widya Hartati; Sandy Ari Wijaya (Institute Of computer Science (IOCS), 2024)
Protection of the human rights and legal rights of Indonesian women is implicit in the Preamble to the 1945 Constitution, namely in the fourth paragraph and Principle V (five) and is guaranteed by the Constitution and is clearly regulated in the applicable laws and regulations. However, the fact is that the Government, as a working instrument of the state, has not been truly present to guarantee the lives of women in Indonesia, including the right to life, work rights, social security, and work protection for women who are still victims of physical violence and sexual violence. So that Indonesia must be present to improve itself in maintaining the dignity of women, both regulations and employment opportunities, as well as a decent life for women towards a civilized country through the Pancasila Perspective Welfare State. Furthermore, this type of research is normative with a qualitative model while still paying attention to empirical problems with document collection techniques and previous research results.